Keragaman Genetik dan Kekerabatan Genotip Kacang Bambara (Vigna subteranea L.) Lokal Jawa Barat - Sobari, Enceng; Wicaksana, Noladhi (Jurnal AGRO, 2017)
Bambara groundnut (Vigna subteranea L.) is one of underutliized crops in Indonesia. Bambara groundnut is potential to be developed and can be utilized as an alternative food source in Indonesia. Bambara groundnut greatly varies and has a very wide area of adaptation. The experiment was conducted at the experimental field station at Ciparanje in Padjadjaran University. Starting on September 2014 until March 2015 with Randomized Block Design (RBD) and repeated two times. The research used 30 accessions originally from various locations in West Java (Bandung, Tasikmalaya, Garut, Sumedang, Bogor, Majalengka) and East Java (Lamongan, Madura). Genetic variability of Bambara groundnut landrace Â in some West Java showed broad criteria on the characters fresh pod weight, dry pod weight, weight of 100 seeds, and weight per plot. Genotypes which had many similarities in some characters based on euclidian distance coefficient had close relationship.